Prevalence of ischaemic heart disease and risk factors in Sri Lanka - Katulanda, P.; Liyanage, I.K.; Caldera, R.; Constantine, G.R.; Sheriff, M.H.R.; Matthews, D.R. (My University, 2010)
To determine the prevalence of ischemic-heart-disease (IHD) and its risk factors. We also aimed to study how the common risk factors contribute to IHD in Sri Lankan adults. Methods: A nationally representative cross sectional was carried out in 2005 recruiting 4,484 individuals. Data were collected using a detailed questionnaire, a clinical examination and investigations (ECG and biochemical investigations). Individuals were defined as having IHD if they had ECG evidence of cardiac ischaemia or had positive Rose Angina questionnaire (RAQ) or on treatment for IHD. Results: Age, sex standardized prevalence of IHD was 9.3% (Male - 7.2%, Female - 11.3%). RAQ was positive in 2.0% and ECG evidence of ischaemia was seen in 7.2%. The following risk factors were identified: hypertension 1212.6%, one or more lipid abnormality 37.0%, smoking 18.4%, physical inactivity 14.1%, obesity 8.9%, diabetes 11.5% and family history of IHD 22.9%. For both males and fen1ales, higher odds-ratios for IHD were seen with hypertension, diabetes and inactivity. Having Multiple risk factors significantly increased the risk of having IHD. Conclusions: This study showed a high prevalence of IHD in Sri Lanka. Early identification and correction of the risk factors may provide an opportunity for early intervention and effective prevention of IHD.
Sri Lanka Medical Association - 123rd Annual Academic Sessions : 2010 ; 53p.